Factors Related To The Incidence Of Stunting In Toddlers Aged 24-59 Months In The Region Work Of UPT Puskesmas Sawah Besar Central Jakarta - Ernawati, Ernawati; Yurita Mailintina; Khalida Ziah Sibualamu; Fitri adella; Keisha Ayu (Sean Institute, 2024)
The incidence of stunting in toddlers is one of the nutritional problems globally. Based on UNICEF data 2012-2018, the prevalence of stunting in the world reached 28%, in Eastern and Southern Africa by 40%, and in South Asia by 38%. When compared to the limit of